Strategi Pemasaran Produk Simpanan Qurban Koperasi Syariah Mitra Usaha Ideal (KOPSYAH MUI) Cabang Dukun Gresik - Muhammad Yusuf Aria Widjaja; Nurul Istifadhoh (STEI Kanjeng Sepuh Gresik Jawa Timur, 2023)
The chance for KOPSYAH MUI to expand is due to the rise in financial institutions selling financial products and participating in financial literacy initiatives. This study aims to evaluate the KOPSYAH MUI sacrificial savings products' marketing approach. Members who want to pay in installments or save for the Eid al-Adha holiday should use sacrificial savings programs. This research is a field study that employs qualitative methodologies to describe information about the research object based on actual field observations. procedures for gathering data that include interviewing, observation, and documentation. The findings demonstrated that the KOPSYAH MUI branch in Dukun successfully adopted a marketing plan for products for sacrificial savings using a number of techniques. The marketing strategy used by KOPSYAH-MUI first applies segmentation, targeting, and positioning. Second, KOPSYAH MUI has a unique marketing strategy for sacrificial savings products that involves joint contact between branch managers and account managers with the public, industry participants, and partners. Fast marketing that does not require members to visit the service bureau is made possible by this socializing.